2014
DOI: 10.3892/ol.2014.2311
|View full text |Cite
|
Sign up to set email alerts
|

Icotinib inhibits the invasion of Tca8113 cells via downregulation of nuclear factor κB-mediated matrix metalloproteinase expression

Abstract: Icotinib is an epidermal growth factor receptor tyrosine kinase inhibitor, which has been revealed to inhibit proliferation in tumor cells. However, the effect of icotinib on cancer cell metastasis remains to be explained. This study examines the effect of icotinib on the migration and invasion of squamous cells of tongue carcinoma (Tca8113 cells) in vitro. The results of the Boyden chamber invasion assay demonstrated that icotinib reduced cell invasion, suppressed the protein levels of matrix metalloproteinas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…These results confirmed that IRX5 activated the NF‐κB pathway by targeting OPN promoter. MMP2 acts as downstream of NF‐κB in cancers, where it degrades the ECM, which is a pivotal step in tumour metastasis and invasion . In our study, MMP2 was up‐regulated by IRX5/OPN signalling, which partially explains the promoting effect of IRX5 in TSCC.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…These results confirmed that IRX5 activated the NF‐κB pathway by targeting OPN promoter. MMP2 acts as downstream of NF‐κB in cancers, where it degrades the ECM, which is a pivotal step in tumour metastasis and invasion . In our study, MMP2 was up‐regulated by IRX5/OPN signalling, which partially explains the promoting effect of IRX5 in TSCC.…”
Section: Discussionsupporting
confidence: 52%
“…Our results indicated that IRX5 overexpression resulted in increased nuclear p65 level and led to increased IκBα degradation. Furthermore, levels of MMP2, which acts as the downstream of the NF‐κB pathway, were also elevated in IRX5 overexpressing cells. Consistent with these results, the knockdown of IRX5 expression using shRNA resulted in decreased nuclear p65, MMP2 expression and IκBα degradation (Figure A).…”
Section: Resultsmentioning
confidence: 97%
“…In fact, in the present study, the MMP-1 expression was nonsignificantly decreased in the metastatic lymph nodes. There have been several studies associating NF- κ B with MMPs suggesting that migratory genes may support NF- κ B in inflammation and carcinogenesis [ 23 , 24 , 34 ]. Considering that NF- κ B triggers many extracellular events like tumor angiogenesis, it is very likely to have a relation with MMP-1.…”
Section: Discussionmentioning
confidence: 99%
“…Radiation has been found to induce migration and invasion, 285 and treatment with invasion inhibitors during radiation therapy could potentially enhance its efficacy. 286,287 Inhibitors targeting EGFR, 288 Na 275 Src, 91 and microtubules 289 can inhibit invasion at concentrations that are not toxic to cells and could be useful in counteracting radiation-induced spread. …”
Section: Discussionmentioning
confidence: 99%